The ringtones an effective way toimprove english listening skills! - Ramos Pineda, Camilo Andrés (Negonotas Docentes, 2013)
Teachers constantly complain about the use of cell phones in classroom. This aspect has become a distraction because students are all the time messaging on facebook, messenger, twitter or any other social networking site. This combination of music benefits and cell phones use in classrooms motivated the author to carry out thisresearchat Universidad la Gran Colombia with students of sixth semester of the B.A. English Program, in 2011.